Study on the Effect of Reciprocating Pump Pipeline System Vibration on Oil Transportation Stations - Hongfang Lu; Xiaonan Wu; Kun Huang (Energies, 2018)
Due to the periodic movement of the piston in the reciprocating pump, the fluid will cause a pressure pulsation, and the resulting pipeline vibration may lead to instrument distortion, pipe failure and equipment damage. Therefore, it is necessary to study the vibration phenomena of reciprocating pump pipelines based on pressure pulsation theory. This paper starts from the reciprocating pump pipe pressure pulsation caused by a fluid, pressure pulsation in the pipeline and the unbalanced exciting force is calculated under the action of the reciprocating pump. Then, the numerical simulation model is established based on the pipe beam model, and the rationality of the numerical simulation method is verified by indoor experiments. Finally, a case study is taken as an example to analyze the vibration law of the pipeline system, and vibration reduction measures are proposed. The following main conclusions are drawn from the analysis: (1) unbalanced exciting forces are produced in the elbows or tee joints, and it can also influence the straight pipe to different levels; (2) in actual engineering, it should be possible to prevent the simultaneous settlement of multiple places; (3) the vibration amplitude increases with the pipe thermal stress, and when the oil temperature is higher than 85 °C, it had a greater influence on the vertical vibration amplitude of the pipe.